Feasibility, Efficacy, and Safety of Percutaneous Muscle Biopsies in Patients With Chronic Liver Disease - Quinlan, Jonathan I.; Dhaliwal, Amritpal; Williams, Felicity; Allen, Sophie L.; Breen, Leigh; Greig, Carolyn A.; Lord, Janet M.; Armstrong, Matthew J.; Elsharkawy, Ahmed M. (Frontiers in Physiology, 2022)
Introduction: Sarcopenia is present in many chronic disease states including decompensated end stage liver disease (ESLD) and non-cirrhotic non-alcoholic fatty liver disease (NAFLD). Sarcopenia in ESLD can negatively impact quality of life and increase mortality. Despite this, very little is understood about the mechanisms of sarcopenia in these conditions. One key reason for this is the reluctance to undertake percutaneous muscle biopsies due to the perceived increased risks. ESLD can induce thrombocytopenia and coagulopathy which significantly increases the risk of bleeding. In addition, patients with either NAFLD or ESLD often have co-morbidities that would require additional care and risk assessment. Thus, the aim of this study was to establish an effective and safe protocol for the implementation of percutaneous muscle biopsies in patients with NAFLD and ESLD. Methods: 47 patients with ESLD and 9 patients with non-cirrhotic NAFLD were recruited from the Liver Unit, Queen Elizabeth Hospital (Birmingham, UK). A total of 71 percutaneous vastus lateralis biopsies were attempted over two study visits. A vigorous safety screening occurred prior to and during each visit and a strict protocol was followed to mitigate against complications and risk. Results: 85% of patients consented to the muscle biopsy at either visit (48/56). 9% of consented biopsies could not occur due to medical considerations, including high INR (n=3) and the use of aspirin (n=4). Muscle tissue was obtained from 90% of attempts, with a mean average yield (wet weight tissue) of 98.1±52.9mg. Conclusion: Percutaneous muscle biopsies are both feasible and yield sufficient tissue in an ESLD population. The procedure is effective for obtaining muscle tissue whilst also safe, with only one adverse event. This study provides evidence for the successful use of muscle biopsies in this population, even in consideration of disease specific complications, medications, and comorbidities.